2000
DOI: 10.1080/10715760000301141
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of DNA damage in apoptosis induced by quercetin and luteolin

Abstract: Quercetin has been reported to have carcinogenic effects. However, both quercetin and luteolin have anti-cancer activity. To clarify the mechanism underlying the carcinogenic effects of quercetin, we compared DNA damage occurring during apoptosis induced by quercetin with that occuring during apoptosis induced by luteolin. Both quercetin and luteolin similarly induced DNA cleavage with subsequent DNA ladder formation, characteristics of apoptosis, in HL-60 cells. In HP 100 cells, an H2O2-resistant clone of HL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…The involvement of ROS has been proposed as upstream event occurring during treatment with high (micro-molar) concentrations of trans-resveratrol [1,21], as well as with other polyphenols, including epigallocatechin-3-gallate [44,53), woodfordin I [35] and quercetin [33,64]. In our experimental system ROS burst occurs precociously (within the first hour) and the detrimental effects produced were confirmed by the increase in lipid peroxidation by-products, MDA and 4-HNE.…”
Section: Trans-resveratrol Induce a Selective Activation Of Jnk And Pmentioning
confidence: 74%
“…The involvement of ROS has been proposed as upstream event occurring during treatment with high (micro-molar) concentrations of trans-resveratrol [1,21], as well as with other polyphenols, including epigallocatechin-3-gallate [44,53), woodfordin I [35] and quercetin [33,64]. In our experimental system ROS burst occurs precociously (within the first hour) and the detrimental effects produced were confirmed by the increase in lipid peroxidation by-products, MDA and 4-HNE.…”
Section: Trans-resveratrol Induce a Selective Activation Of Jnk And Pmentioning
confidence: 74%
“…However, the actions of flavonoids are complex and often seemingly antagonistic or paradoxical. For example, while flavonoids are described as antioxidant agents protecting against oxidative insults to cells and apoptosis [11,13,88], others have found flavonoids to be pro-oxidants and -apoptotic [33,212,221]. Thus, it becomes clear that the effects of flavonoids depend on different factors such as the specific compound used, the cell type, concentrations, experimental design, and the general context in which flavonoids are used.…”
Section: Biological and Cellular Propertiesmentioning
confidence: 99%
“…Several studies have shown that quercetin is a pro-oxidant and cytotoxic in leukemic cells. 7,8) Flavonoids including quercetin caused apoptosis in carcinoma/cancer cells 2,9) and showed cytotoxicity in normal cells including human umbilical vein endothelial cells.…”
Section: 2)mentioning
confidence: 99%
“…Several studies have shown that quercetin is a pro-oxidant and cytotoxic in leukemic cells. 7,8) Flavonoids including quercetin caused apoptosis in carcinoma/cancer cells 2,9) and showed cytotoxicity in normal cells including human umbilical vein endothelial cells.10) The neuronal density of the hippocampus in gerbils subjected to infusion of quercetin to the ventricle was significantly lower than that in control.11) Thus, the effects of quercetin on cell death and/or apoptosis in cells including neuronal cells have not been well confirmed.The PC12 cell line, a rat adrenal medullary pheochromocytoma, is a useful model for studying the survival of neuronal cells. Native PC12 cells divide and resemble precursors of adrenal chromaffin cells and sympathetic neurons when grown in the presence of serum, and gradually attain the phenotypic properties of sympathetic neurons on the addition of nerve growth factor (NGF).…”
mentioning
confidence: 99%
See 1 more Smart Citation